The electroacoustic music in the school: outlining perspectives under the sociocultural approach of musical education - Stoeberl da Cunha, Daiane Solange [UNESP] (Univ Federal Goias, 2017)
This article presents the sociocultural perspective of music education as an important instrument for the analysis of music in school culture. It focuses on the discussion about aspects of this theoretical approach applied to the theme of teaching electroacoustic music in schools. Among the authors that base this reflection we highlight: Geertz (1989), Tia DeNora (2000), Arroyo (2002, 2013), Green (1997, 2012), Small (2009), Stockfeld (1997), Elliott (1995), Jorgensen (1997), Allsup (2010). Finally, we suggest some arguments to comprehend the challenges and possibilities of teaching face to an innovative musical repertoire.
Keywords: Musical education; Sociocultural Perspective; Electroacoustic Music; Basic education